INJURY PATTERNS IN MOTOR VEHICLE ACCIDENT CASES IN SLEMAN BASED ON SLEMAN HDSS DATA 2021 - Salsabila Bianda Sheillashahna; Idha Arfianti Wiraagni; Hendro Widagdo; Martiana Suciningtyas (Menara Medika, 2024)
Background: Analysing injury patterns is crucial for preventing a decline in productivity and quality of life. Every year, thousands of lives are lost due to motor vehicle accidents. Data from HDSS Sleman 2021 is used in this study to support scientific development in the health sector. HDSS aims to build surveillance sites, generate quality data, and support evidence-based community services. Problem: The presence of numerous traffic accident cases in the HDSS Sleman 2021 data highlights the importance of analysing their injury patterns. Objectives: The research will be carried out to determine the pattern of injury in motor vehicle accident cases in Sleman based on HDSS data year 2021. Method: Descriptive observational study using cross-sectional method. The data collected is HDSS Sleman secondary data. All injury cases listed in the HDSS Sleman document for the year 2021 were used as research participants. Secondary data analysis was conducted to determine the pattern of injury. The descriptive method will be used to analyse the data. Result: The total sample of this study is 302 people. The sex predominance of motor vehicle accident cases is in male (62%). It is mostly found in the age of 25-64 years old (55%). Out of 302 samples, the highest prevalence of site of injury location in victim body is lower extremity and the lowest is stomach/internal organ. The highest prevalence of injury type is bruises and the lowest are limb severation, concussion, and burn injury. Conclusion: Based on the analysis conducted from the Health and Demographic Surveillance System (HDSS) Sleman data for the year 2021, the most common injuries occurred in the lower extremities, affecting 208 individuals (69%), with bruises being the predominant injury type. Among all traffic accident victims in the HDSS Sleman 2021 dataset, bruises were the most prevalent injury type, affecting 257 individuals (85%). From the Chi-Square analysis that has been carried out, there is a statistically significant correlation between chest injury and gender which has a p-value of 0.008. There was also a statistically significant correlation between sprained and gender which had a p-value of 0.012, eye injury and gender which had a p-value of 0.028.